Novel phthalocyanines containing azo chromophores; synthesis, characterization, photophysical, and electrochemical properties - Garip, Ebru Özkan; Özçeşmeci, Mukaddes; Nar, Ilgın; Özçeşmeci, İbrahim; Hamuryudan, Esin (World Scientific Pub Co Pte Lt, 2018)
A series of novel metal-free and zinc (II), copper (II), cobalt (II), and manganese (III) phthalocyanine complexes bearing peripheral 2,6-dimethyl-4-(4-tert-butyl-phenylazo)phenoxy units have been synthesized. Novel phthalonitrile derivative required for the preparation of these phthalocyanine complexes was prepared by a base-catalyzed nucleophilic aromatic nitro displacement of 4-nitrophthalonitrile with 2,6-dimethyl-4-(4-tert-butyl-phenylazo)phenol. The structures of these new compounds were characterized by using elemental analyses, proton and carbon nuclear magnetic resonance, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy and mass spectrometry. The photophysical properties of metal-free and zinc(II) phthalocyanines were studied in tetrahydrofuran. The electrochemical properties of the phthalocyanine complexes were investigated by cyclic and square wave voltammetry.